Biosurfactants produced by Scheffersomyces stipitis cultured in sugarcane bagasse hydrolysate as new green larvicides for the control of Aedes aegypti, a vector of neglected tropical diseases - Franco Marcelino, Paulo Ricardo; Silva, Vinicius Luiz da [UNESP]; Philippini, Rafael Rodrigues; Von Zuben, Claudio Jose [UNESP]; Contiero, Jonas [UNESP]; Santos, Julio Cesar dos; Silva, Silvio Silverio da (Public Library Science, 2017)
Biosurfactants are microbial metabolites with possible applications in various industrial sectors that are considered ecofriendly molecules. In recent years, some studies identified these compounds as alternatives for the elimination of vectors of tropical diseases, such as Aedes aegypti. The major bottlenecks of biosurfactant industrial production have been the use of conventional raw materials that increase production costs as well as opportunistic or pathogenic bacteria, which restrict the application of these biomolecules. The present study shows the potential of hemicellulosic sugarcane bagasse hydrolysate as a raw material for the production of a crystalline glycolipidic BS by Scheffersomyces stipitis NRRL Y-7124, which resulted in an emulsifying index (EI24) of 70 +/- 3.4% and a superficial tension of 52 +/- 2.9 mN.m(-1). Additionally, a possible new application of these compounds as biolarvicides, mainly against A. aegypti, was evaluated. At a concentration of 800 mg.L-1, the produced biosurfactant caused destruction to the larval exoskeletons 12 h after application and presented an letal concentration (LC50) of 660 mg.L-1. Thus, a new alternative for biosurfactant production using vegetal biomass as raw material within the concept of biorefineries was proposed, and the potential of the crystalline glycolipidic biosurfactant in larvicidal formulations against neglected tropical disease vectors was demonstrated.